Jalan Panjang Menuju Inklusi Digital bagi Penyandang Disabilitas di Indonesia - Poerwanti, Sari Dewi; Makmun, Sukron; Dewantara, Amhar Davi (Universitas Wijaya Kusuma Surabaya, 2024)
Currently, the trend of internet use continues to increase, including in Indonesia. The internet is believed to be able to support community empowerment and improve welfare. For this reason, digital technology is required to be able to reflect the needs of all levels of society, including people with disabilities. This is a great opportunity for people with disabilities to benefit from digital information, products and services to live more independent lives. This article discusses how digital technology, especially the internet, is used by people with disabilities, including the obstacles that accompany it. This research uses a literature review method by collecting data through observation and literature study. The research results show that there is a digital gap between people with disabilities and non-disabled people in Indonesia. The main obstacles in creating an inclusive digital space are awareness, motivation, access to ownership, access to use, access to affordability of digital technology, digital skills, adaptive technology, certainty of digital protection & security as well as policy and regulatory support. However, efforts were also found to implement good digital inclusion practices by reducing the digital divide through policy support, infrastructure improvements, empowerment activities and increasing public awareness.Keywords: people with disabilities; digital inclusion; digital divide; digital technology